The Influence of Notables in Building Civilization National and Religious Loyalty as a Model - Ahmed Mafhoum; Ahmed Al-Razzaqi; Abdul Basit Al Baraka; Abdelhak el idrissi (MAQOLAT: Journal of Islamic Studies, 2025)
. The manifestations of notables in the contemporary political field have become more established, especially the notables of tribes who were more closely connected to the people, so some of them exploited their relationship with the people in an outrageous manner to reach political positions and win the electoral bet. We also record the migration of notables to political positions at the expense of social functions and their societal reform and cultural tasks, perhaps in response to the brilliance of politics or of course in achieving their economic goals or managing their enterprises by gaining the relationships of officials and their companionship in preparation for tax evasion. We also record that the orientalists were confused and did not agree on the meaning of notables and their tasks throughout history according to the degree of bias they had and the intended purpose behind the study.